2002
DOI: 10.1080/10473289.2002.10470783
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Three-Dimensional Modeling of Airflow and Pollutant Dispersion in an Undersea Traffic Tunnel

Abstract: Airflow and pollutant dispersion in a cross-harbor traffic tunnel were experimentally and numerically studied. Concentrations of the gaseous pollutants CO, NO x , and total hydrocarbons (THC) at three axial locations in the tunnel, together with traffic flow rate, traffic speed, and types of vehicle were measured. Three-dimensional (3D) turbulent flow and dispersion of air pollutants in the tunnel were modeled and solved numerically using the finite volume method. Traffic emissions were modeled accordingly as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The problem is rather difficult to handle here due to the 3D geometry of the vehicles. Previous work by Chen et al (2002) modeled the piston effect of vehicle by having the fluid on the floor moving with the average traffic speed on the floor, thus resulting in an overestimate of fluid speed near the tunnel floor due to the neglect of non-slip conditions. However, tunnel studies by Chen, Lee, and Hsu (1998) indicated that the piston effect of vehicle causes the airflow to move at a speed approximately equal to the vehicle speed at a distance, z p ≒ 0.0625H, from the floor.…”
Section: Modeling Of Roughness and Piston Effect Of Vehiclesmentioning
confidence: 99%
See 2 more Smart Citations
“…The problem is rather difficult to handle here due to the 3D geometry of the vehicles. Previous work by Chen et al (2002) modeled the piston effect of vehicle by having the fluid on the floor moving with the average traffic speed on the floor, thus resulting in an overestimate of fluid speed near the tunnel floor due to the neglect of non-slip conditions. However, tunnel studies by Chen, Lee, and Hsu (1998) indicated that the piston effect of vehicle causes the airflow to move at a speed approximately equal to the vehicle speed at a distance, z p ≒ 0.0625H, from the floor.…”
Section: Modeling Of Roughness and Piston Effect Of Vehiclesmentioning
confidence: 99%
“…Chen et al (2002) simulated undersea traffic-tunnel flow and pollutant dispersion using the standard set of model constants. As to be seen later, because the dominant flow is unidirectional from tunnel inlet to tunnel outlet and traffic-tunnel flow is usually of low Reynolds number turbulent flow, the use of the standard k-e model is adequate in this study.…”
Section: Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature measurements by Louka et al 29 in an urban street found that ⌬T is ϳ3 K at 9 a.m. and ϳ9 K at 6 p.m., and ⌬T ϭ 5 K was investigated numerically by Sini et al, 26 which are all commensurate with the range of 0 -5 K herein. The logarithmic function for a roughness wall was used in the velocity wall function, the same as that used in Chen et al 32 Also, the Jayatilleke function was used in the temperature wall function, the same as that in Kim and Baik. 27,36 The street roughness is specified as 3.8 cm, the same as in the previous work.…”
Section: Model Domain and Boundary Conditionsmentioning
confidence: 99%
“…The procedures to estimate from the measured traffic flow rates have been described in related studies. 23,32 First, the rate of emission q ik (t) by traffic in the kth lane, of species i, is determined by:…”
Section: Numericalmentioning
confidence: 99%